ANALISIS KONTRIBUSI DAN EFEKTIVITAS RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BREBES - Absor, Ulul (PERMANA, 2014)
This study aims to determine the contribution levy on revenue market Brebes and to determine the level of effectiveness of the market levy on revenue Brebes. Market acceptance of the 2010-2014 levy each year has increased, which is reflected on the income levy receipts Brebes market between 2010 to 2014 already meet the targets and even exceed the predetermined targets, with an average target is met by 102,54 percent. While acceptance Brebes local revenues increased by an average increase of 31.21 percent. Brebes PAD highest rise occurred in 2014 in the amount of 51.90 percent and the lowest occurred in 2011 amounted to 10.21 percent. Whereas in 2012 and in 2013 amounted to 30.06 percent and 32.66 percent. While the level of effectiveness of retribution market during the period 2010-2014 as a whole is very effective. This is reflected in actual revenues that always exceed or exceeds the set target. The average value of the level of achievement of the target for 5 (five) last year amounted to 102.52 %. This shows that the effectiveness of marketretribution is very effective .